2011
DOI: 10.1088/0022-3727/44/36/365406
|View full text |Cite
|
Sign up to set email alerts
|

Effect of temperature on the stability of dielectric elastomers

Abstract: Dielectric elastomer (DE) is a kind of electroactive polymer material, capable of large deformation up to 380%. However, under conservative operating conditions, DE is susceptible to instability with a small deformation due to various modes of failure, including electrical breakdown, electromechanical instability (EMI), loss of tension and rupture by stretch. This paper proposes a free energy model in the thermodynamic system of DE involving thermoelastic strain energy, electric energy and purely thermal contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 32 publications
0
32
0
Order By: Relevance
“…The free energy model of the thermodynamic system can be expressed as rightW(λ1,λ2,ξ1,ξ2,T,D)=TT0Wstretch(λ1,λ2,ξ1,ξ2)+ρ0c0[TT0Tln(TT0)]+trueD22ɛ(T)λ12λ22 …”
Section: Working Principle Of Dielectric Elastomersmentioning
confidence: 99%
See 2 more Smart Citations
“…The free energy model of the thermodynamic system can be expressed as rightW(λ1,λ2,ξ1,ξ2,T,D)=TT0Wstretch(λ1,λ2,ξ1,ξ2)+ρ0c0[TT0Tln(TT0)]+trueD22ɛ(T)λ12λ22 …”
Section: Working Principle Of Dielectric Elastomersmentioning
confidence: 99%
“…The equilibrium stretch λe increases with the increase of the external force, but slightly decreases with the increase of temperature. If a large force is applied on the membrane at a low temperature, the equilibrium stretch λe can be very large, which may result in a failure model known as rupture by stress …”
Section: Working Principle Of Dielectric Elastomersmentioning
confidence: 99%
See 1 more Smart Citation
“…, and 100 m J = for VHB 4910 dielectric elastomer [12,14,17] . Figure 2(a) shows that the prestress value is high at high temperature.…”
Section: Eletromechanical Instabilitymentioning
confidence: 99%
“…But few reports have been released on the effect of temperature on actuation and instability of dielectric elastomer. Our previous study indicated that the increase in temperature can markedly contribute to improving the entropy production and the critical nominal electric field of the DE [17] . Recently, Liu et al [18] studied the thermo-electro-mechanical instability of dielectric elastomers by employing a Mooney-Rivlin model, but used independently determined value for the dielectric constant.…”
Section: Introductionmentioning
confidence: 99%